2021
DOI: 10.1093/mnras/stab1578
|View full text |Cite
|
Sign up to set email alerts
|

TESS cycle 1 observations of roAp stars with 2-min cadence data

Abstract: We present the results of a systematic search for new rapidly oscillating Ap (roAp) stars using the 2-min cadence data collected by the Transiting Exoplanet Survey Satellite (TESS) during its Cycle 1 observations. We identify 12 new roAp stars. Amongst these stars we discover the roAp star with the longest pulsation period, another with the shortest rotation period, and six with multiperiodic variability. In addition to these new roAp stars, we present an analysis of 44 known roAp stars observed by TESS during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 212 publications
(403 reference statements)
1
6
0
Order By: Relevance
“…The relation between rotation period and roAp pulsations is not yet known, hence the increased sample provides more data to examine this. Holdsworth et al (2021) found that 68% of the 56 roAp stars with TESS data show rotational modulation from spots. This is useful for precise determination of the rotation period, but it is only for stars with Prot < ∼ 22 d, as a consequence of the 27-d TESS sectors.…”
Section: A7 Be Star Historymentioning
confidence: 98%
See 4 more Smart Citations
“…The relation between rotation period and roAp pulsations is not yet known, hence the increased sample provides more data to examine this. Holdsworth et al (2021) found that 68% of the 56 roAp stars with TESS data show rotational modulation from spots. This is useful for precise determination of the rotation period, but it is only for stars with Prot < ∼ 22 d, as a consequence of the 27-d TESS sectors.…”
Section: A7 Be Star Historymentioning
confidence: 98%
“…This problem has become clear in photometry from TESS observations of roAp stars, particularly HD 6532 , and also other stars (Holdsworth et al 2021). The amplitudes of the multiplet frequencies generated by oblique pulsation provide information about the mode geometry.…”
Section: Nonlinear Pulsation: Combination Frequencies -Opportunities ...mentioning
confidence: 99%
See 3 more Smart Citations